A STUDY OF METAPHOR IN UZBEK LINGUISTICS - Normuminov Laziz (Galaxy International Interdisciplinary Research Journal, 2022)
This article analyzed scientific research on the study of metaphor, considered the concept of metaphor, its anthropocentric nature, private-author metaphors and their names created in the fiction text.